Lessons for Jurisdictional Approaches From Municipal-Level Initiatives to Halt Deforestation in the Brazilian Amazon - Brandão, Frederico; Piketty, Marie-Gabrielle; Poccard-Chapuis, René; Brito, Brenda; Pacheco, Pablo; Garcia, Edenise; Duchelle, Amy E.; Drigo, Isabel; Peçanha, Jacqueline Carvalho (Frontiers in Forests and Global Change, 2020)
Jurisdictional approaches have become popular in international forums as promising strategies to reduce greenhouse gas emissions caused by deforestation and to guarantee sustainable commodity supply. Yet, despite their growing popularity, up to now, there is little consensus on how such approaches should move forward in specific jurisdictions. In this paper we examine two contrasting municipal-level case studies in the eastern Amazonian state of Para where jurisdiction-wide efforts are underway to reduce deforestation. By developing detailed environmental governance timelines since 2005, conducting semi-structured interviews with key informants, analyzing municipal deforestation trends, plus extensive examination of project reports, governmental documents and other secondary sources, this paper performs two main analyses. First, it characterizes the processes in each municipality by linking the context and the environmental governance timeline to deforestation trends. Second it provides a systematic comparison of processes based on (1) the role of the government, (2) multi-stakeholder participation and inclusiveness, (3) adaptive governance, (4) horizontal and vertical coordination, and (5) alignment of public and private (supply-chain) initiatives. In so doing, this article answers some of the imperative questions on how to implement and improve jurisdictional approaches aimed at halting deforestation in the tropics.